Sensorimotor Experience Influences Recovery of Forelimb Abilities but Not Tissue Loss after Focal Cortical Compression in Adult Rats - Martinez, Marina; Brezun, Jean-Michel; Xerri, Christian (PLOS ONE, 2011)
Sensorimotor activity has been shown to play a key role in functional outcome after extensive brain damage. This study was aimed at assessing the influence of sensorimotor experience through subject-environment interactions on the time course of both lesion and gliosis volumes as well as on the recovery of forelimb sensorimotor abilities following focal cortical injury. The lesion consisted of a cortical compression targeting the forepaw representational area within the primary somatosensory cortex of adult rats. After the cortical lesion, rats were randomly subjected to various postlesion conditions: unilateral C5–C6 dorsal root transection depriving the contralateral cortex from forepaw somatosensory inputs, standard housing or an enriched environment promoting sensorimotor experience and social interactions. Behavioral tests were used to assess forelimb placement during locomotion, forelimb-use asymmetry, and forepaw tactile sensitivity. For each group, the time course of tissue loss was described and the gliosis volume over the first postoperative month was evaluated using an unbiased stereological method. Consistent with previous studies, recovery of behavioral abilities was found to depend on post-injury experience. Indeed, increased sensorimotor activity initiated early in an enriched environment induced a rapid and more complete behavioral recovery compared with standard housing. In contrast, severe deprivation of peripheral sensory inputs led to a delayed and only partial sensorimotor recovery. The dorsal rhizotomy was found to increase the perilesional gliosis in comparison to standard or enriched environments. These findings provide further evidence that early sensory experience has a beneficial influence on the onset and time course of functional recovery after focal brain injury.